Integrated Approaches to Pain Management - Deolekar, Pradnya; Dongerkery, Kavitha; Deolekar, Sandesh; Deolekar, Prathmesh (Disease and Health: Research Developments Vol. 10, 2025)
Pain is a multifaceted and personal experience shaped by a range of physical, psychological, and social elements. This review presents a comprehensive overview of pain classification, its underlying mechanisms, and contemporary management techniques. It delves into pharmacological interventions—including non-opioid analgesics, opioids, adjuvant medications, and topical treatments—as well as non-pharmacological strategies such as cognitive-behavioral therapy, physical rehabilitation, and complementary therapies. The document also evaluates the effectiveness of the WHO analgesic ladder and emphasizes the significance of personalized, multimodal approaches to enhance patient care. Pain is a subjective experience that involves physical, psychological, and social factors. According to the International Association for the Study of Pain (IASP), pain is defined as an unpleasant experience (sensory and/or emotional) related to a potential or confirmed tissue damage. It can arise from a variety of sources, including injury, disease, inflammation, and nerve damage. The word "pain," derived from the Latin "poena" meaning punishment, has historically been viewed as a divine consequence for human sins. Physician Albert Schweitzer stated in 1931 that "pain is a more terrible lord of mankind than even death itself." Pain perception and management have evolved from ancient remedies, such as acupuncture and herbal medicine, to modern anesthetics like morphine and aspirin. Treatments vary widely in effectiveness due to individual differences in pain thresholds; what relieves pain for one person may be less effective for another.